CRISPR-mediated generation of a tumor-associated antigen-deficient Raji platform to investigate antigen loss in CAR-T cell therapy - Iyer, Aditya Ramdas; Nafiz, Mehwish; Gupta, Pragya; VR, Arvinden; Saravanakumar, Vinodh; Ansari, Mohammad Sufyan; Shakir, Md; Ahmad, Tanveer; Ramalingam, Sivaprakash (Frontiers in Genome Editing, 2025)
Tumor-associated antigen (TAA) loss remains a significant mechanism of resistance to chimeric antigen receptor (CAR) T cell therapy, leading to relapse in patients with B-cell malignancies and representing a major clinical challenge. Recent clinical data suggest that CD19 antigen loss triggers relapse in more than 40% of patients undergoing CD19 CAR-T cell therapy. To rigorously validate antigen loss, robust in vitro models that mimic the dynamic process of antigen escape are essential. However, the current absence of these models hampers our ability to fully evaluate and optimize treatment strategies. To model this clinically relevant phenomenon, we generated single (sKO), double (dKO), and triple (tKO) knockout Raji lymphoma cell lines targeting CD19, CD20, and CD22 using CRISPR/Cas9 genome editing. Initially, we established a dual-reporter cell line expressing the fluorescent marker mCherry and the bioluminescent marker Luciferase, enabling a uniform luminescence background across all the knockout cell lines before performing the CRISPR/Cas9 editing. The loss of individual or combinatorial TAAs was validated at the genomic, transcript, and protein levels. Functional co-culture assays with antigen-specific CAR-T cells showed that antigen-deficient Raji cells resisted CAR-T cell-mediated killing, closely mimicking clinical relapse. The triple knockout (tKO) model, in particular, provided a superior system compared to commonly used K562 models, as it retains the same lymphoma background while eliminating the crucial antigenic targets, thus better simulating resistance to CAR-T cell therapy. These antigen-loss models serve as valuable tools for studying mechanisms of CAR-T cell resistance and evaluating next-generation, multi-targeting CAR-T cell therapies.